Kikuchi Disease of Parotid Gland (JBN (Jurnal Bedah Nasional), 2025)
Aim: Kikuchi disease, often referred to as Kikuchi–Fujimoto disease (KFD), is an uncommon benign cervical lymphadenitis etiology.  Cervical lymphadenopathy is Kikuchi disease's most prevalent clinical sign. The incidence of Kikuchi disease is reported more in young adult women. Case Presentation: We report a rare instance of parotid gland Kikuchi-Fujimoto disease (KFD). A 36-year-old woman presented to our department with a left preauricular tumor that had been present for three weeks. His Ultrasound revealed a well-defined anechoic cystic lesion with solid components in the preauricular area of the left jugular upper. FNAB was done and the results was an adenoma pleiomorfik with supurative inflammation. The patient underwent parotidectomy surgery and specimens sent to pathologic anatomic department. Patient confirmed with Kikuchi disease of parotid gland based on pathologic examination. Conclusion: Although rare, Kikuchi disease can be manifest in parotid gland and mimic parotid gland neoplasm. Complete assessment must be done to make right diagnosis to give appropriate treatment to the patient.
Keywords: Kikuchi disease; parotid gland neoplasm; pathologic examination